Placenta-Derived Osteoprotegerin Is Required for Glucose Homeostasis in Gestational Diabetes Mellitus - Huang, Binbin; Zhu, Wen; Zhao, Huashan; Zeng, Fa; Wang, Esther; Wang, Hefei; Chen, Jie; Li, Mengxia; Huang, Chen; Ren, Lirong; Niu, Jianmin; Zhang, Jian V. (Frontiers in Cell and Developmental Biology, 2020)
Osteoprotegerin (OPG) is involved in various biological processes, including bone remodeling, vascular calcification and pancreatic β-cell function. Although some clinical studies have shown an increase in serum OPG level during pregnancy, the role of OPG in gestational diabetes mellitus (GDM) is largely unknown. Therefore, we explored the effect of OPG in metabolic homeostasis during pregnancy. We initially evaluated serum OPG levels using ELISA and western blotting techniques on samples from GDM patients. We also assessed OPG expression levels in maternal mice. We then used blastocysts transduced with lentiviruses capable of trophoblast-specific transgene expression to establish placenta-specific OPG knockdown or overexpression mouse models for functional and mechanistic investigation after embryo transplantation. We found that OPG expression was positively associated with GDM in clinical samples, and OPG levels were significantly increased in GDM patient sera and term placenta. Serum OPG was significantly increased in maternal compared to nonpregnant mice, and expression levels of OPG were the highest in placenta compared with other organs, including bone, liver and pancreas. OPG was also significantly increased in pregnant mice fed a high-fat diet (HFD). Placenta-specific OPG knockdown induced glucose intolerance, decreased β-cell proliferation and decreased serum insulin levels, whereas placenta-specific OPG overexpression promoted glucose tolerance and enhanced β-cell proliferation, which increased serum insulin production and decreased fetal weight in HFD-feeding pregnant mice. Placenta-derived OPG (pl-OPG) regulated glucose homeostasis during pregnancy via enhancement of β-cell proliferation, which suggests a potential therapeutic application of OPG for GDM.